In search of the missing Robert Mangaliso Sobukwe - Hayes, Grahame (PINS-Psychology in Society, 2024)
Benjamin Pogrund (2015 – new edition) How can man die better: The life of Robert Sobukwe. Johannesburg & Cape Town: Jonathan Ball Publishers (1990). ISBN 978-1-86842-681-2 pbk. Pages 427 There is a certain pathos at the heart of the story of neglect that Robert Sobukwe has suffered in South Africa’s political history, and especially so since the advent of democracy in 1994. It seems that he is remembered, in a few street names and such, so that he can quickly be forgotten! And yet, Sobukwe and his ideas, refuse to be removed from the fabric of everyday consciousness, as though their ghostly presence haunts our political conscience. In the last few years there have been many short articles that either invoke the name and significance of Sobukwe, or are directly trying to make a case for his continuing relevance and importance in South Africa’s contemporary political scene (see amongst others, Ndletyana, 2013; Gqola, 2014; Lebelo, 2015; Pogrund, 2015; Maserumule, 2016; Mkhwanazi, 2016).